Association of the coronary artery disease risk gene GUCY1A3 with ischaemic events after coronary intervention - Keßler, Thorsten; Wolf, Bernhard; Katus, Hugo (Cardiovascular research, 2019)
AbstractAim. A common genetic variant at the GUCY1A3 coronary artery disease locus has been shown to influence platelet aggregation. The risk of ischaemic even